Hubungan Tingkat Pendidikan terhadap Pengetahuan pada Pedagang Tahu Putih tentang Kandungan Formalin di Pasar Tradisional Kota Surabaya - Ashlikhatul Khanif; Trias Mahmudiono (Media Gizi Kesmas, 2023)
Background: Tofu is an alternative food known to be delicious and nutritious but has a short shelf life. Sellers use formalin as a preservative because it is more economical, cheaper, and readily available. Formalin if consumed continuously can cause health problems. The use of formalin in tofu can be caused by a lack of knowledge about the dangers of formalin. One's knowledge can be influenced by one's education. Objectives: This study aims to analyze the relationship between education level and knowledge of white tofu sellers about formalin content in traditional markets in Surabaya. Methods: The research was conducted on May 31-June 13, 2022 in Surabaya traditional market. This type of research was analytical observational with a cross-sectional approach. The research sample of 46 traders was taken using multistage random sampling technique. Interviews used a questionnaire containing 12 multiple choice questions. Qualitative test of formaldehyde content using MQuant Formaldehyde Test. Statistical analysis used chi-square test with a significance of 0.05. Results: This study found that most traders had primary and junior high school education (60.9%) and lacked knowledge about formalin (41.3%). Qualitative test results showed no tofu samples containing formalin (100%). Conclusions: There was a significant relationship between the level of education and respondent's knowledge (p=0.043).